Pendampingan Kewirausahaan Digital Mahasiswa melalui Program Reseller Properti pada Mitra PT Commeasure Solutions Indonesia (Reddoorz Indonesia) - Muhammad Liksiara Arjuna Sakti Pamungkas; Ika Korika Swasti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The development of digital entrepreneurship creates new business opportunities for students; however, many still have limited knowledge and skills in utilizing digital platforms for business activities. This community service program aimed to provide digital entrepreneurship assistance to student organizations through a property reseller program in partnership with PT Commeasure Solutions Indonesia (RedDoorz Indonesia). The methods applied included community education, training, diffusion of technology, and advocacy through mentoring in the use of the RedSeller application and guidance in room promotion via Facebook. The results showed that participants were able to complete account registration, conduct promotional activities, and generate initial room booking transactions. This assistance program effectively enhanced students’ digital entrepreneurial skills and opened sustainable technology-based business opportunities.